2016
DOI: 10.1111/iej.12653
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glass fibre post length and remaining dentine thickness on the fracture resistance of root filled teeth

Abstract: Reduced dentine thickness in roots with longer posts had lower fracture resistance values, as catastrophic failure was more predominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 37 publications
3
36
0
2
Order By: Relevance
“…Despite all the benefits, fiber posts serve only to create adequate retention for the resin composite core to support a full crown. This indication is similar to metal posts, in which previous preparation of the root canal is required, involving removal of part of the endodontic obturation and widening of the canal, thereby possibly decreasing the fracture resistance of dental remnants [6]. Conversely, when a minimum amount of dental remnant exists, it allows for an adhesive interface between enamel and cement, enabling an endocrown restoration to be used [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the benefits, fiber posts serve only to create adequate retention for the resin composite core to support a full crown. This indication is similar to metal posts, in which previous preparation of the root canal is required, involving removal of part of the endodontic obturation and widening of the canal, thereby possibly decreasing the fracture resistance of dental remnants [6]. Conversely, when a minimum amount of dental remnant exists, it allows for an adhesive interface between enamel and cement, enabling an endocrown restoration to be used [7].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behavior of these teeth may vary according to the features of the posts, such as their manufacturing material. [ 19 ] Various studies have shown that teeth restored with metallic posts show a higher prevalence of catastrophic fracture patterns. [ 19 20 ] On the contrary, a repairable pattern of fracture was observed in roots restored with fiber posts, especially glass fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous tests are available for evaluating the mechanical properties of posts and cores [15][16][17][18] . In the present study, static fracture load test was performed to compare the mechanical stability of endocrowns and post-cores.…”
Section: Discussionmentioning
confidence: 99%